2015
DOI: 10.2176/nmc.oa.2014-0324
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Hanger Reflex Occurrence: Unexpected Head Rotation on Fronto-temporal Head Compression

Abstract: When the head is encircled with a wire clothes hanger and the unilateral fronto-temporal region is compressed, the head rotates unexpectedly. As the mechanism is unclear, however, we have temporarily named this phenomenon as the “hanger reflex.” We previously reported a case wherein this phenomenon was applied to treat cervical dystonia. Because little is known about this phenomenon, we determined how often this phenomenon is observed in healthy subjects. Study participants were 120 healthy Japanese adults (60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“… 15) We previously reported that more than 90% of healthy volunteers experienced a rotating sensation of the head after fronto-temporal compression, indicating that the HR is common in healthy subjects. 13) In the present study, a majority of subjects (85.4%) exhibited the HR in the direction of the compressed side; moreover, the HR restricted abnormal head rotation related to CD. In a previous study, the device was shown to generate sufficient pressure on the fronto-temporal region to restrict pathological head rotation even after its use for only 1 month.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“… 15) We previously reported that more than 90% of healthy volunteers experienced a rotating sensation of the head after fronto-temporal compression, indicating that the HR is common in healthy subjects. 13) In the present study, a majority of subjects (85.4%) exhibited the HR in the direction of the compressed side; moreover, the HR restricted abnormal head rotation related to CD. In a previous study, the device was shown to generate sufficient pressure on the fronto-temporal region to restrict pathological head rotation even after its use for only 1 month.…”
Section: Discussionsupporting
confidence: 49%
“…In our previous research, the HR was absent in 7.9% of the 240 trials from 240 volunteers. 13) On this basis, non-responders to HR induction may have a more obtuse angle at the temporal line, making it difficult to induce skin shearing force. Our co-authors tentatively named this phenomenon (with unknown mechanism) the “hanger reflex” in 2008.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Movies 1-5 are available online.). [1][2][3] This phenomenon first came to light publicly in 1995, when a television program in Japan reported that a man aimlessly wore a wire hanger around his head while he was studying and found that his head rotated. After publication in a book, this phenomenon was termed as the "hanger reflex" by Kajimoto et al at the University of Electro-Communications in 2008.…”
Section: Introductionmentioning
confidence: 99%
“…(A) A wire hanger used to induce the hanger reflex and (B) the hanger is stretched out and worn around the head, touching the frontotemporal area and causing a sensation of the head rotating toward the compressed side. These figures have been reproduced from previously published papers 2,6).…”
mentioning
confidence: 99%